Women Left Behind: Migration, Agency, and the Pakistani Woman - Ahmed, Sarah (Gender & society, 2020)
This article examines how migration impacts power dynamics and gender norms for women left behind living in rural Southern Punjab, Pakistan, a site where patriarchal customs and religion are interwoven to confine women’s mobility and agency. Based on qualitative interviews and focus groups with women left behind from 2015 through 2018, this article explores how local rural-to-urban male migration patterns impact the decision-making powers of women who are left behind and must make sense of the family structure and gender dynamics in their homes after their husbands’ exit. This study finds that in the absence of her migrant husband, a woman left behind is still subject to patriarchal norms and surveillance by the remaining in-laws, including other women. Citing specific examples from the field, I explain why women left behind remain close to the very families that confine and monitor their movement, and why, in some cases, women left behind turn a blind eye toward their husband’s second or third marriage. Through an examination of behind-the-scenes negotiations that women left behind make, I argue that women maintain for themselves at surface level the gendered expectations that patriarchy sets for them, but given the opportunity, they can negotiate and bargain their positionality in subtle ways without disrupting the status quo that could otherwise jeopardize their physical safety and social reputation (honor).